Adopsi dan Penerimaan Teknologi AI: Tinjauan Sistematis Berdasarkan Model UTAUT - Anggi R., Novia; Hapsari, Inas Ulfa; Irwansyah, Irwansyah (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) developed by Venkatesh et al. (2003), as a perspective to understand the factors that influence the acceptance of Artificial Intelligence (AI) technology in various aspects of life. This model has been used in various studies to analyze the behavioral intentions of technology users. The method in this study is a literature review, by selecting and analyzing 30 accredited scientific journals published between 2019 - 2025. This study aims to analyze the acceptance and implementation of AI technology and its implications for communication dynamics. The results of the study have important implications for AI technology being accepted and implemented in various sectors. The suggestion that can be offered through this study is to develop strategies to overcome obstacles that may be encountered in the process of technology acceptance and adaptation. One concrete step that can be taken is to provide training or provision aimed at technology users.Keywords: Artificial Intelligence, UTAUT, Technology acceptance, Technology adoption, Systematic literature review.